Impact of video-assisted thoracic surgery versus open thoracotomy on postoperative wound infections in lung cancer patients: A systematic review - Helvy Susanti (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Lung cancer remains a leading cause of cancer-related mortality worldwide, with surgical resection being the primary curative approach for early-stage non-small cell lung cancer. Postoperative wound infections following thoracic surgery significantly impact patient outcomes, healthcare resources, and quality of life. Purpose: To evaluate the incidence, risk factors, management, and outcomes of postoperative wound infections comparing Video-Assisted Thoracic Surgery (VATS) versus open thoracotomy in lung cancer patients. Method: A systematic review with article selection guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The systematic review process begins with the formulation of clinical questions relevant to the topic. Before this, the authors establish PICOS criteria, which stand for: P (problem, patient, or population), I (intervention, prognostic factor, or exposure), C (comparison or control), O (outcome), and S (study design). For this article, P: Adult patients with diagnosed lung cancer who underwent surgical resection, I: Video-Assisted Thoracic Surgery (VATS), C: Open thoracotomy, O: Incidence of postoperative wound infections, infection severity, causative microorganisms, time to infection development, treatment approaches, and impact on hospital stay, S: Randomized controlled trials. The article search was conducted systematically using the keywords: